Conifer wood assemblage dominated by Podocarpaceae, early Eocene of Laguna del Hunco, central Argentinean Patagonia - Pujana, Roberto R.; Wilf, Peter; Gandolfo, Maria A. (PhytoKeys, 2020)
During the early Eocene, Patagonia had highly diverse floras that are primarily known from compression and pollen fossils. Fossil wood studies from this epoch are scarce in the region and largely absent from the Laguna del Hunco flora, which has a highly diverse and excellently preserved compression assemblage. A collection of 26 conifer woods from the Laguna del Hunco fossil-lake beds (early Eocene, ca. 52 Ma) from central-western Patagonia was studied, of which 12 could be identified to genus. The dominant species is Phyllocladoxylon antarcticum, which has affinity with early-diverging Podocarpaceae such as Phyllocladus and Prumnnopitys. A single specimen of Protophyllocladoxylon francisiae probably represents an extinct group of Podocarpaceae. In addition, two taxonomic units of cf. Cupressinoxylon with putative affinity to Podocarpaceae were found. Diverse Podocarpaceae taxa consistent with the affinities of these woods were previously reported from vegetative and reproductive macrofossils as well as pollen grains from the same source unit. Some of the woods have galleries filled with frass. Distinct growth ring boundaries indicate seasonality, inferred to represent seasonal light availability. Growth ring widths suggest that the woods came from mature trees, whereas the widths and types of some rings denote near-uniform temperature and water availability conditions.